CEO Overconfidence, Audit Fee, and Audit Report Lag - Sumunar, Kurnia Indah; Anita, Anita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
A Financial statements must be presented in timely manner because the information will be used by investors for decision making. Audit report lag can be caused by audit fee and the role of CEO in decision making. The purpose of this study is to examine the mediating role of audit fees on the effect of CEO Overconfidence to audit report lag. Many studies only examine the effect of audit fees without paying attention to CEO's psychological condition. This study uses a sample of companies listed on the IDX from 2016 to 2020 that obtained through the official website of IDX and Thomson Reuter Database. The results show that CEO Overconfidence has a negative effect on audit report lag mediated by audit fees. CEO Overconfidence will choose to report financial statements in timely manner by increasing audit fees so that the image as CEO who can make good decisions can be proven.